Unionization and Profitability in the Canadian Manufacturing Sector - Laporta, Pasquale; Jenkins, Alexander W. (Relations industrielles / Industrial Relations, 1996)
A study looks at the effects of unions on profitability in the Canadian manufacturing sector, taking into account structural factors such as concentration and entry barriers. It is found that, although there is a moderately positive relationship between unionization and profitability at low levels of concentration, at higher levels of concentration unions are able to extract an increasing proportion of incremental profits that the firm (industry) may earn, until any incremental profit (rent) associated with further increase in industry concentration is completely captured by the union. This may reflect a greater ability on the part of unions to organize and exercise bargaining power in concentrated industries and redistribute income from capital to labor, but it also leads to underproduction and resource misallocation.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Finance; Labor; Labor Unions; Manufacturers; Manufacturing; Profitability; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Standard deviation; Studies; Unionization